Down to the roots of lemmings: a new species of basal lemming from the upper Pliocene of West Siberia. Issue 5 (30th March 2022) - Tesakov, Alexey; Bondarev, Alexey
ABSTRACT: A previously unknown evolutionary stage of true lemmings, Lemmini, is recorded in the lower upper Pliocene (early Villanyian, MN16a) of West Siberia. Tobienia fejfari, sp. nov. represents a more advanced evolutionary stage than the previously known European Tobienia kretzoii (late Ruscinian, MN15b), combining rhizodont molar teeth with extreme hypsodonty, crown cement, and occlusal morphology resembling the earliest lemming with rootless molars, Plioctomys, of later Late Pliocene age (MN16b). The new discovery contributes to our knowledge of early stages in the formation of the high latitude mammalian fauna of Eurasia.